Experimental evaluation of antiulcer activity the prophylactic use of placenta cryoextract on model of ethanol-prednisolone gastric lesion - Кошурба, І.В. (Abstract book of the scientific-practical conference with international participation «Young science 4.0» (2022 May 30, Kyiv). 2022. Р. 34., 2022)
Gastric and duodenum ulcer is the one of the most common diseases of the internal organs. As a potential gastroprotective agent, our attention was drawn to the cryopreserved extract of human placenta, because the literature convincingly demonstrated that this cryoextract eliminates the ulcerogenic action of nonsteroidal anti-inflammatory drugs, which has a mechanism similar to peptic ulcer disease. The aim of the study was to characterize the gastroprotective activity of cryopreserved placenta extract under the prophylactic regimen of use in the model of ethanol-prednisolone gastric lesions in rats. Materials and methods. The study was performed on 28 male rats weighing 200–220 g. Gastric lesions in rats were simulated by intragastric single administration of prednisolone (20 mg/kg) dissolved in 80.0% ethanol (0.6 ml/100 g body weight). Cryoextracts of the placenta were administered intravenously in a prophylactic mode – 1 time per day for 5 days before the introduction of ethanol-prednisolone mixture. In 24 h. after administration of the mixture, rats were removed from the experiment and the size of the stomach (bloating) and the presence of adhesions with adjacent organs were evaluated macroscopically by the following criteria: erosions and hemographies, hyperemia, edema and mucosal fold disorders. For each group, the percentage of experimental animals was calculated according to these characteristics and the average value of their severity. The values of the ulcer index were calculated for each group. Research results and their discussion. The introduction of ethanol-prednisolone mixture causes erosive ulcerative lesions of the gastric mucosa in 100% of rats The introduction of cryoextract placenta significantly reduced the damaging effect of ulcerogenic mixture on the mucous membrane, advice on the performance of control rats. The severity of antiulcer activity of the studied cryoextract in the prophylactic mode of use is statistically significantly (p<0.05) exceeds the similar effect of esomeprazole. Conclusions. Prophylactic five-day administration of cryopreserved placenta extract is accompanied by a statistically significant (p<0.05) marked gastroprotective effect in a model of ethanol-prednisolone gastric lesions in rats.
Koshurba I. Experimental evaluation of antiulcer activity the prophylactic use of placenta cryoextract on model of ethanol-prednisolone gastric lesion. Abstract book of the scientific-practical conference with international participation «Young science 4.0» (2022 May 30, Kyiv). 2022. Р. 34. DOI: https://doi.org/10.5281/zenodo.6580979.
Keywords: antiulcer activity; placenta cryoextract; ethanol-prednisolone gastric lesion